PRODUKTIVITAS DAN BIAYA PEMANENAN KAYU DI HUTAN TANAMAN RAWA GAMBUT - Sona Suhartana; Yuniawati Yuniawati (Lambung Mangkurat University-Indonesia, 2016)
Logging activities typifies as early stage of timber production. Loggings exert essential roles in removing logs from inside forests to locations for wood industries or customers. In relevant, research was already conducted in 2013 that took place in Satria Perkasa Agung Company with intent to look into productivity and cost of loggings carried out at peat swamp plantation forests. Field data that comprised productivity and cost of loggings at each of their specified aspects (i.e. felling, skidding, loading-unloading, and hauling) were processed into tabulation forms for the calculation of their means (averages) and standard deviation values. Results revealed that in averages: (1) productivity of tree felling which used MS-381’s machine was 8 m3/hour; (2) skidding productivity that employed Hitachi Zaxis’ excavator machine reached 5.899 m3/hour; (3) loading and unloading productivity using consecutively Kobelco SK 2000-8’s excavator and Komatsu PC 300’s excavator machines corresponded to 87.292 m3/hour and 88.735 m3/hour, respectively; (4) productivity of log hauling that used barge and pontoons was 116.379 m3/hour, while the one using truck reached 111.602 m3/hour; and ultimately (5) appropriate and right selection of equipment for wood loggings could enhance their productivity and concurrently minimize their production cost. Kegiatan pemanenan kayu merupakan tahap awal dari produksi kayu. Pemanenan kayu berperan penting guna mengeluarkan kayu dari dalam hutan menuju lokasi industri atau konsumen. Penelitian dilaksanakan pada tahun 2013 di PT Satria Perkasa Agung, bertujuan untuk mengetahui produktivitas dan biaya pemanenan kayu di hutan tanaman rawa gambut. Data lapangan berupa produktivitas dan biaya pemanenan dari masing-masing aspek (yaitu penebangan, penyaradan, muat bongkar dan pengangkutan), diolah ke dalam bentuk tabulasi untuk dihitung rata-ratanya. Hasil penelitian menunjukkan bahwa : (1). Rata-rata produktivitas penebangan menggunakan Stihl MS-381 adalah 8 m3/jam; (2) Rata-rata produktivitas penyaradan menggunakan ekskavator Hitachi Zaxis 110 adalah 5,899 m3/jam; (3) Rata-rata produktivitas muat dan bongkar menggunakan ekskavator Kobelco SK 200-8 dan ekskavator Komatsu PC 300 masing-masing adalah 87,292 m3/jam dan 88,735 m3/jam; (4) Rata-rata produktivitas pengangkutan kayu dengan sampan besi dan pontoon 116,379 m3/jam serta menggunakan truk 111,602 m3/jam; dan (5) Pemilihan alat yang tepat pada pemanenan kayu dapat meningkatkan produktivitas dan meminimalkan biaya produksi.